Scientific research in the Antarctic treaty system - Gozhik, P. F.; Gurzhiy, A. M.; Lytvynov, V. A. (Ukrainian Antarctic Journal, 2009)
The report highlights the most important initiatives put forward by SCAR in the Concept "Antarctic Science in the XXI century". Taking into consideration that the Antarctic Science becomes increasingly complex and expanding in the geographical dimension, in the XXI century the international cooperation and partnership will be required in areas, such as: - Joint infrastructure and logistics; - Expanding of the geographical presence; - Joint research, technology, standardization of methods and measurement, international data bases and research results archives. The examples are given in what way the Antarctic Scientific Programs, in particular, of United States, Great Britain, Argentina, Ecuador ensure the national interests of these states in Antarctica and in the Antarctic Treaty System. The correlation is pointed between national (Ukrainian) Antarctic Programs with the research main orientations of the SCAR Concept for examples both of the State Program of Ukrainian Researches in Antarctic in 2002-2010 and the Concept draft of the new State Scientific-Technical Program of the Ukrainian Researches in Antarctica in 2011-2020.